(untitled) (Fiep Bulletin - online, 2014)
The Hall Dancing beginning was in the middle age as a kind of court dancing. Its social and pedagogical nature is healthy and it can be used for pleasure, partnership, body-mind association, socialization, prophilaxy and treatment, practiced in balls, parties, gyms, SPA’s and medical clinics. The aim of this project is promote understanding of historical-social aspects such as the individual or group perception, development of the hall dancing basis by the musical and silence stimulus, individual and group respect, the perception of body limits when experiencing the movements, enthusiasm for overcoming their own limits, understanding of the hall dancing expression in the school context; educating the citizen through the hall dancing. The researching studying group was composed of students in the 2nd and 3rd grades of Secondary Education of John Kennedy Estate School, Aracaju city - Sergipe. The sample was composed by sixty-nine people between 17 - 43 old, the both sex. The group was applied a project which has as content the hall dancing for a period of six months. Then, we analyzed the hall dancing benefits in the students learning. With this intention, we observed the classes and got information through interviews. So, with this research we could realize that the hall dancing as a physical education content has arouse interest, pleasure and it has increased their socialization process. In fact, we understand that in the hall dancing the learners find an option to increase their social, cultural and educative repertoire, working and enjoying themselves while they’re learning and improving their rhythm, emotion and social integration, besides to salvage and share culture aspects from our country and world. In face with these results we have to highlight the importance of the Hall Dance such as Physical Education content at Schools.